Analisis Motivasi Kerja Pada Pegawai UPTD 2 Dinas Perumahan Kawasan Permukiman Dan Pertanahan Kota Tangerang Selatan - Budiman, Etong; Kustini, Endang (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Work performance is one of the main problems that really needs to be paid attention to in an institution/organization. At this time, where times continue to change and the economy is always improving, where the human resource system is very dominant, which results in increasingly tight competition between institutions/organizations. SKPD is required to continue to develop and be able to improve services for the community, SKPD must also think about quality aspects and continuously improve the performance of its workforce. Optimal work performance is a reflection of quality human resources. Work performance is the result of work in terms of quality and quantity achieved by an employee in carrying out his main duties and functions as an employee in accordance with the responsibilities assigned or given to him. The ability of each person, system or company to produce something desired by utilizing resources effectively and efficiently.